Quali alterazioni dell'esame urine possono preludere ad un interessamento renale della malattia di Fabry - Sandro Feriozzi; Mario Mangeri (AboutScience Srl, 2019)
The markers of renal involvement in Anderson-Fabry disease are defects of urine concentration, presence of cells with lipid cytoplasmatic inclusions (mulberry bodies) and podocyturia. The loss of urine concentrating capacity is not easy to detect and the search for cellular inclusions is a complex technique. Moreover, none of the markers has any clear correlation with the stage of the disease. The occurrence of podocytes in the urine (podocyturia) correlates with both renal involvement and clinical outcome; therefore, podocyturia seems to be a promising early indicator of nephropathy. However, a common agreement on the laboratory assay used to measure is still needed.